Robust Measures of Core Inflation for Vietnam - Kalra, Sanjay (IMF Working Papers; Working Paper ;, 2016)
The paper develops robust measures of core inflation for Vietnam that can be used in policy making. These core inflation measures (CIMs) are based on an analytical evaluation of the inflation process in Vietnam, and use a filtering approach to narrow down potential measures that satisfy certain empirically desirable criteria. The paper finds that commonly used exclusion-based measures (EBMs) do not perform well against these empirical criteria; trimmed mean measures (TMMs) do better. Among TMMs, 'one trim does not fit all periods'; periods of high and variable inflation require larger trims, and conversely. EVIEWS and MATLAB programs which accompany the paper allow quick, timely replication of CIMs as new data become available, making them valuable tools for the State Bank of Vietnam on an ongoing basis.